Keluarga sebagai Pendidikan Pertama Anak; Memaksimalkan Peran Orangtua dalam Tumbuh Kembang Anak Usia 1-4 Tahun - Ubaidillah (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2020)
The family is the closest environment that children have. The family is part of the first and foremost educational institution for children, because it is through families that children learn, grow and develop. All aspects of child development need to be stimulated and supported by parents, especially at the smallest level of the environment, the family. These aspects of child development include the development of religious and moral values, aspects of physical motor development, cognitive development, language development, social emotional development, and aspects of artistic development. Parents need to know aspects of the child's development, so that they can provide appropriate stimulation in the family environment. By knowing aspects of child development, parents are expected to create a conducive family environment in order to maximize the child's growth and development. Children's social relationships will develop through interaction with family at home. This social relationship will further develop through interaction with peers when the child is at school. The more often a child interacts with others, the more skills his children have in developing relationships together with others. Parents have a very important role to always stimulate and direct the growth and development of children. Children's togetherness experiences with parents, are the basis for future play activities. Children who have a good relationship with their parents will find it easier to play together with others. It will be easier to adapt to other environments. Children aged 1-4 years is a very vital period in the growth and development of children. Children have aspects of development that require stimulation and support from all parties, both parents, teachers in children's educational institutions, and the environment in which children live. The family is the first school for children, so the role of the family is important for further child development. Good habits are part of instilling character and positive things that parents can do as the child's first teacher. Introducing a new environment, including introducing children with new friends such as entering pre-school world, is also an important part that must be done by parents so that children are able to adapt well. Planting positive character values, will make it easier for children to enter the next stage of development in a child's life, so that the child is ready to enter the next life development.